An Interreligious Initiative for Peace and Harmony: A Christian Perspective - Cherian, Joyson K (Transformation, 2019)
Spiritual energy and power can be purposefully used to create structures and conditions that allow religious communities to co-exist. In the context of South Asia and particularly of India, can the very presence of Christians become a gift to the community? A useful pointer could be revisiting the concept of Jubilee Year as described in Leviticus, Isaiah and Luke that portrays the message of atonement, restoration, hospitality and renewal of the divine covenant - all of which are essential for inter-religious dialogue. The following paper seeks possible answers by addressing the concerns of the Christian layman and building up a framework for inter-religious dialogue, with a focus on being faithful to the Christian Gospel. The aim is to create conditions in which different accounts of the world of human experience can flourish together.